Religion in cinema : Buddhism and Taoism in popular films through a jungian lens - Low, Yuen Wei (2014)
In this thesis, Buddhist and Taoist approaches to the development of “Self” and its relation to the human being’s conscious and unconscious minds, and the Jungian viewpoint of Self form an interdisciplinary framework to study the images and ideologies of these religions in popular films. Contents from both religions that are portrayed in popular films are discussed; symbols and philosophy from Buddhism and Taoism in relation to the Jungian perspective of archetypes and universal symbols within popular films are examined. This research is drawn from the fields of psychology and religion, and as such, contributes to an interdisciplinary outreach of research in film studies. It examines Buddhism and Taoism in a selection of five popular films, two of which are produced by Hollywood, while the remaining three are Chinese-language productions. Textual analysis through a Jungian perspective is carried out on Crouching Tiger, Hidden Dragon (2000) directed by Ang Lee, The Karate Kid (2010) directed by Harald Zwart, The Promise (2005) directed by Chen Kaige, Seven Years in Tibet (1997) directed by Jean-Jacques Annaud, and Hero (2002) directed by Zhang Yimou. The thesis concludes that the cinema allows viewers to go through a journey of individuation similar to that undergone by the protagonists of the films. While traveling together with the characters in the space of the cinema, viewers are presented with ideologies and symbols from Buddhism and Taoism that have the potential to bring about transformations in their own minds. The cinema thus allows viewers to look at the characters on the screen with conscious identification or even judgment, and at the same time, allows the unconscious aspect to go through a journey of individuation together with the characters presented.